Town planning in the Netherlands since 1800 - Wagenaar, Cor (International Planning History Society Proceedings, 2016)
This article summarizes part of the gist of Town Planning in the Netherlands since 1800. Responses to Enlightenment Ideas and Geopolitical Realities, a book that discusses Dutch urbanism in its international setting, dividing its contents in a series of clusters that are presented as being determined by geopolitics, ideology, and planning. The timeframe of over 200 years (400 years if the prologue is included) highlights continuities and discontinuities that otherwise would have been lost – a strong motive in favor or writing books instead of articles. It defines urbanism as a combination of spatial planning (distributing human activities across space in cities, regions and on the global level) and design (one of its uses being that of a billboard for local identity, the community, the nation or political ideologies). In the two centuries of urban planning presented here, the Netherlands had to re-invent itself several times. Dutch urban history is marked by changes on the international scene, the prevailing political ideals, the development of modern planning as a distinct discipline and the continuous changes of the main countries that inspired Dutch planning – France until the 1830s, Germany from the 1830s to the 1930s, and since the 1930s increasingly the United States. The years between 1795 and 1815 marked the end of an era: though the nation still clung to the idea that it could play an important role in the world’s political affairs, its days as a ‘hyper power’ - to quote Amy Chua - were numbered. Nothing illustrated this more vividly than the run-down state of most of its cities. Especially in the province of Holland, many had become a faded imagine of their former self: comparing maps made during the so-called Golden Age with the brand new cadaster maps that had been ordered by the national government in the early nineteenth century, nobody could escape the impression that for almost two hundred years, nothing had changed. Some cities, for instance Enkhuizen, had even lost a large part of their inhabitants and demolished part of their buildings... In 1815 the Netherlands definitely abandoned the political structure that had characterized it in its heydays: the federal republic was replaced by a unitary state headed by a king, William I, a representative of the Orange family the fate of which was closely connected to the Netherlands since it gained independence in the late sixteenth century. William I, who had spent many years in England, embarked upon an ambitious campaign that should restore the country to its former glory, an ambition sparkled by the merger with the Southern Netherlands (now Belgium). Canals were dug and new roads, subdivided according to a French inspired classification system, were built that connected the two re-united states, accepting the distinct nature of both: the former Republic was expected to revitalize an economy based on trade, banking and agriculture, whereas the Southern half continued to promote industry. Combined with many other differences - the North was Calvinist and bourgeois, the South was Catholic and here the aristocracy never lost its privileged position - the merger proved untenable and after a short civil war, Belgium became independent (and subsequently developed into the continent’s first industrial state). William’s revanchist policies caused economic stagnation in the Northern half, the huge investments in its infrastructure proved futile.